Concentrations and human health risks attributed to potentially toxic elements (PTEs) in water resources in China: Systematic review and meta-analysis - Xiaomei Hui; Anhui Li; Sheng Chang; Aihua Wang; Lu Wang; Chao Li (Ecotoxicology and Environmental Safety)
Long-term exposure to potentially toxic elements (PTEs) increases carcinogenic and non-carcinogenic risks in the exposed population. The current study was conducted with the aims of meta-analysis concentrations of PTEs including Arsenic (As), Cadmium (Cd), Lead (Pb), Mercury (Hg), Nickel (Ni) and Copper (Cu) in the water resources and human health risk assessment for adult males and female consumers in China. Search was performed in international databases including Web of Science, Scopus, PubMed, Embase and Google Scholar (gery literature) from January 1, 2005 to April 1, 2024. The concentration of PTEs was meta-analyzed using random effects model in water resources (surface water and groundwater) and location of study (urban and rural locations) subgroups. Human health risk assessment due to PTEs in water from ingestion and dermal contact pathways was estimated using target hazard quintet (THQ) and carcinogenic (CR) in adult males and female consumers in China. One hundred and twenty-six papers with 237 data-reports (n = 13,083) were included in this study. The rank order of PTEs based on pooled concentration was As (12.6530 µg/l) > Cu (11.1810 µg/l)> Ni (2.4950 µg/l) > Pb (2.0660 µg/l) > Cd (0.5370 µg/l) > Hg (0.3600 µg/l). The rank order of PTEs based on percentage studies higher than standard limits was As (28.37 %) > Pb (16.67 %) > Hg (11.86 %) > Ni (9.91 %) > Cd (7.48 %) > Cu (2.38 %). The pooled concentration of Pb, Ni, Hg and Cu in surface water resources was higher than groundwater but concentration of As and Cd in groundwater water was higher than surface water. The rank order of PTEs based on percentage studies with the high non-carcinogenic risk (THQ ≥ 1) for male was As (30.49 %) > Cd (8.09 %)> Hg (6.90 %) > Ni (3.60 %)> Cu (3.39 %) > Pb (2.50 %) and for female, As (29.78 %) > Cd (8.09 %)> Hg (6.90 %) > Cu (3.39 %) > Ni (2.70 %)> Pb (1.25 %). The rank order of PTEs based on percentage studies with high carcinogenic risk (TCR ≥ 1E-4) for male was As (60.28 %) > Cd (33.33 %) and for female, As (56.73 %) > Cd (29.93 %). Therefore, to reduce the carcinogenic and non-carcinogenic risks of PTEs especially As, continuous monitoring and control release of As into water resources through novel approaches is recommended.